VD_FINDINFO AP / 2010 / 194 vom 30. Juni 2010 - VD Tribunal cantonal (2010)
ACTION EN CONSTATATION, MEILLEURE FORTUNE, DROIT DES POURSUITES ET FAILLITES | 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 92 CPC, 265 al. 2 LP, 265a al. 4 LP, 265a LP, 41 al. 1 let. a LVLP, 41 al. 2 LVLP, 41 LVLP